Upaya Pemenuhan Hak-Hak Keperdataan Anak Yang Lahir di Luar Perkawinan - Ahmad Baihaki (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2023)
Protection of children's rights is a constitutional mandate that must be guaranteed so that children can grow and develop to become the next generation of quality nations in the future. However, in reality, in contrast to legitimate children, children born outside of marriage are often denied their civil rights. This paper aims to examine arrangements regarding protection and legal remedies that can be used in the context of fulfilling the civil rights of children outside of marriage according to Islamic law and positive law in Indonesia. This research was conducted using normative juridical research methods by collecting secondary data sources and analyzed descriptively qualitatively using conceptual, statutory, and comparative approaches. Based on the research results, although the constitution in general has provided guarantees for the protection of children's rights. However, until now there are no statutory regulations or implementing regulations that specifically regulate the civil rights of children born out of wedlock, so they do not provide legal certainty. Efforts to fulfill the civil rights of children outside of marriage to date are still encountering many obstacles, both in terms of legal structure, legal substance, and legal culture so that it is considered that maximum legal protection has not been created for guaranteeing the fulfillment of civil rights of children outside of marriage.